Improvements in Circumpolar Southern Hemisphere Extratropical Atmospheric Circulation in CMIP6 Compared to CMIP5. Issue 6 (16th June 2020) - Bracegirdle, T. J.; Holmes, C. R.; Hosking, J. S.; Marshall, G. J.; Osman, M.; Patterson, M.; Rackow, T.
Abstract: One of the major globally relevant systematic biases in previous generations of climate models has been an equatorward bias in the latitude of the Southern Hemisphere (SH) mid‐latitude tropospheric eddy driven westerly jet. The far‐reaching implications of this for Southern Ocean heat and carbon uptake and Antarctic land and sea ice are key reasons why addressing this bias is a high priority. It is therefore of primary importance to evaluate the representation of the SH westerly jet in the latest generation of global climate and earth system models that comprise the Coupled Model Intercomparison Project Phase 6 (CMIP6). In this paper we assess the representation of major indices of SH extratropical atmospheric circulation in CMIP6 by comparison against both observations and the previous generation of CMIP5 models. Indices assessed are the latitude and speed of the westerly jet, variability of the Southern Annular Mode (SAM), and representation of the Amundsen Sea Low (ASL). These are calculated from the historical forcing simulations of both CMIP5 and CMIP6 for time periods matching available observational and reanalysis data sets. From the 39 CMIP6 models available at the time of writing there is an overall reduction in the equatorward bias of the annual mean westerly jet from 1.9° in CMIP5 to 0.4° in CMIP6 and from a seasonal perspective the reduction is clearest in austral spring and summer. This is accompanied by a halving of the bias of SAM decorrelation timescales compared to CMIP5. However, no such overall improvements are evident for the ASL. Plain Language Summary: Computer models that simulate the position, strength, and spatio‐temporal behavior of winds in the Southern Hemisphere around the continent of Antarctica often show typical errors when compared to reality. This can impact answers to very relevant questions, such as how much heat and carbon are taken up by the ocean or how the sea ice cover will evolve in the future. Here we document how the newly available next generation of global climate models that form the basis for the next Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) performs with respect to observed Southern Hemisphere winds. We also analyze potential improvements compared to the previous generation of computer models. Overall, some important differences to observations (biases) are much smaller than in the previous models (by up to 50%). Other diagnostics are, however, virtually unchanged, which indicates that the improvements are rather limited between model generations. However, our study could help to identify possible reasons for the remaining biases and to further reduce errors in upcoming models. Key Points: Representation of Southern Hemisphere mid‐latitude tropospheric westerlies is improved in the Coupled Model Intercomparison Project Phase 6 Key improvements are a reduced equatorward bias in jet latitude and more realistic timescales of variability There is no clear improvement in the representation of the Amundsen Sea Low